2018
DOI: 10.1016/j.bonr.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of glucocorticoid induced osteonecrosis in the mouse is not affected by treatments that maintain bone vascularity

Abstract: ObjectiveDetermine if LLP2A-Ale or PTH (1–34) affects the prevalence of glucocorticoid-induced osteonecrosis (ON) in a mouse model.MethodsEight-week-old young adult male BALB/cJ mice were weight-randomized into Control (Con), glucocorticoid (GC)-only, or concurrent treatments with GC and LLP2A-Ale (250 μg/kg or 500 μg/kg, IV, Days 1, 14, 28) or parathyroid hormone hPTH (1–34) (40 μg/kg, 5×/week). Mice were necropsied after 45 days for qualitative evaluation of prevalent ON and quantitative evaluation of vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…In a glucocorticoid-treated mouse model that yields an osteonecrosis prevalence of 36%, CD31 and endomucin positive cells declined in glucocorticoid treated mice relative to vehicle. However, while treatment with LLP2A-Alendronate (a bone targeted agent that guides endogenous or exogenous mesenchymal stromal cells to bone) or parathyroid hormone (PTH) increased CD31 and endomucin cells similar to vehicle group, no change in prevalence of osteonecrosis was noted 86. Using different rodent models of osteonecrosis and PTH, other studies have reported an improvement in prevalence of osteonecrosis with a combination treatment of core decompression and PTH, including improvement in neovascularization 87.…”
Section: Type H Vessels In Bone Disordersmentioning
confidence: 99%
“…In a glucocorticoid-treated mouse model that yields an osteonecrosis prevalence of 36%, CD31 and endomucin positive cells declined in glucocorticoid treated mice relative to vehicle. However, while treatment with LLP2A-Alendronate (a bone targeted agent that guides endogenous or exogenous mesenchymal stromal cells to bone) or parathyroid hormone (PTH) increased CD31 and endomucin cells similar to vehicle group, no change in prevalence of osteonecrosis was noted 86. Using different rodent models of osteonecrosis and PTH, other studies have reported an improvement in prevalence of osteonecrosis with a combination treatment of core decompression and PTH, including improvement in neovascularization 87.…”
Section: Type H Vessels In Bone Disordersmentioning
confidence: 99%
“…( 161,162 ) Type H ECs decline in glucocorticoid‐treated mice compared with the vehicle group. ( 163 ) Further, a combination treatment of core decompression and parathyroid hormone (PTH) has been used to promote neo‐angiogenesis and bone repair, decreasing the prevalence of osteonecrosis in mouse models. Nevertheless, further research is required to investigate the benefit of blood vessel targeted therapy under clinical settings of osteonecrosis in humans.…”
Section: Osteonecrosismentioning
confidence: 99%
“…More importantly, we found that the development of ON was independent of bone mass. Specifically, a potent bone anabolic agent, such as PTH, activated osteoblast activity, and increased bone mass but failed to reduce the incidence of ON 30 …”
Section: Discussionmentioning
confidence: 99%